A mixed mode elasto-plastic damage model for prediction of failure in single lap joint. (July 2022) - Ri, Jun-Hyok; Kim, Myong-Ho; Hong, Hyon-Sik
Abstract: In this paper, a pressure-dependent elasto-plastic continuum damage model is derived to account for the elasto-plastic behaviour as well as the gradual damage evolution in the single lap joint (SLJ) using thermodynamic principals. The damage onset is activated by the pressure-dependent loading criterion similar to the yield condition. The total energy release rate is equal to the critical energy release rate as in CZM. This means that the proposed model belongs to a continuum damage model adapting to CZM. However, the present model is different in that it applies the actual pressure-dependent continuum elasto-plastic constitutive relation before the damage onset. Both examples (a symmetric and an asymmetric SLJ) validate that the current model depicts not only the plastic behavior but also damage evolution. An example for the asymmetric SLJ shows that the asymmetric damage evolution and asymmetric crack propagation path in the adhesive layer may be captured using the current model. User material subroutine UMAT in ABAQUS/Standard is used to implement the current model.